Explaining the associations of education and occupation with childlessness: the role of desires and expectations to remain childless - Verweij, RM; Stulp, G; Snieder, H; Mills, MC (Sociological Demography Press, 2021)
Although there are well-established relationships between women’s higher education, labour force participation (LFP), and occupation on the one hand and childlessness on the other hand in the US, the underlying reasons and the role that childlessness desires and expectations play remain unclear. We use the National Longitudinal Survey of Youth in the United States (N=4,198 women) and apply both logistic regression models to examine the role of childlessness desires early in life, and multilevel models for repeated measures to examine the role of childlessness expectations throughout the life course. We find that higher educational attainment and LFP are positively associated with childlessness. We do not find, however, that higher educated and working women more often desire or expect to remain childless. In contrast, we find that among women who ultimately remain childless, those women who work full-time and have higher status occupations have higher expectations to have children throughout their life course. These results suggest that education and occupation produce constraints, resulting in the postponement of childbearing which hinders women in realizing their desires and expectations. Since many working women remain childless despite the desire and expectation to become a mother, our findings stress the importance of work-life reconciliation. It furthermore highlights the importance of increasing public awareness regarding the decrease in fecundity with age.